Granulomatous peritonitis: An under suspected entity in children - Narang, Vishrut; Mittal, Narender Kumar; Kumari, Anita; Garg, Rishi (Indian Journal of Child Health, 2020)
Post-operative granulomatous peritonitis is a rare entity in children. It is a post-operative complication that should be differentially diagnosed in patients who present with abdominal pain, tenderness, and fever after surgery. It closely mimics tuberculosis in both clinical and operative findings and requires histopathological and microbiological examination. Etiologically, post-operative granulomatous peritonitis is observed in patients with a history of surgery, hypersensitive to cellulose fibers, starch, or vegetable matter. Management is done by steroids and anti-inflammatory drugs.